Revival of Landing's Concept of Infantile Obstructive Cholangiopathy A Plea to Hand Over the 2 Week Old Jaundiced Full Term Neonate to the Surgeon! (Journal of Paediatric Surgeons of Bangladesh, 2014)
The concept of infantile obstructive cholangiopathy started in 1974 by Landing and remained till early 1980s. However, the concept has not been used much since then as nothing new has developed over the last 40 years sufficient enough to change the course of the disease or identify its etiology. This review article is an attempt to consolidate evidence on review of literature pointing towards a common etiopathological process leading to the spectrum of anomalies constituting neonatal cholestasis. The importance of early referral of any case with neonatal jaundice in a full term neonate, preferably at 2 weeks age is highlighted. This will help to identify and treat more cases within the correctable range and prevent the disease from progressing to a life threatening situation especially in developing countries where the resources for liver transplantation are meagre.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19465